A research and clinical framework for understanding achilles injury in female collegiate gymnasts - Fryar, C.; Tilley, D.; Casey, E.; Vincent, H. (Current Sports Medicine Reports, 2023)
Gymnastics is a popular sport with a high injury rate, particularly at the collegiate level. Achilles tendon rupture is a catastrophic injury with career-changing impact. Over the last decade, there has been a growing incidence of Achilles tendon ruptures, especially in female gymnasts. Currently, neither the effects of contributing risk factors on Achilles tendon rupture nor the research frameworks to guide future intervention strategies have been well described. This article reviews the functional anatomy and mechanical properties of the Achilles tendon, provides precollegiate and collegiate intrinsic and extrinsic risk factors for Achilles tendon rupture, and proposes a research framework to address this injury from a systemic perspective. Potential clinical interventions to mitigate Achilles tendon injury are proposed based on currently available peer-reviewed evidence.